2011
DOI: 10.1007/s13244-011-0130-3
|View full text |Cite
|
Sign up to set email alerts
|

Gonad shielding in paediatric pelvic radiography: disadvantages prevail over benefit

Abstract: ObjectiveTo re-evaluate gonad shielding in paediatric pelvic radiography in terms of attainable radiation risk reduction and associated loss of diagnostic information.MethodsA study on patient dose and the quality of gonad shielding was performed retrospectively using 500 pelvic radiographs of children from 0 to 15 years old. In a subsequent study, 195 radiographs without gonad shielding were included. Patient doses and detriment adjusted risks for heritable disease and cancer were calculated with and without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 28 publications
2
54
0
5
Order By: Relevance
“…Liakos et al (2001) reported that only 1.6% of pelvic radiographs had the correct placement of gonad shields (14). The results of this study are worrying as the importance of gonad shielding has been well established in the literature (4,6,11). It seems that, in procedures in which gonads are exposed in the primary beam, it is difficult to correctly position the gonad shields so that gonads are completely obscured whilst not concealing important anatomical data (4,6,7,11).…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Liakos et al (2001) reported that only 1.6% of pelvic radiographs had the correct placement of gonad shields (14). The results of this study are worrying as the importance of gonad shielding has been well established in the literature (4,6,11). It seems that, in procedures in which gonads are exposed in the primary beam, it is difficult to correctly position the gonad shields so that gonads are completely obscured whilst not concealing important anatomical data (4,6,7,11).…”
Section: Discussionmentioning
confidence: 82%
“…The results of this study are worrying as the importance of gonad shielding has been well established in the literature (4,6,11). It seems that, in procedures in which gonads are exposed in the primary beam, it is difficult to correctly position the gonad shields so that gonads are completely obscured whilst not concealing important anatomical data (4,6,7,11). MacKay et al (2012) believed that "one of the main reasons for omission of the gonad shield is a lack confidence or skill in the gonad shield placement of radiographers and the attitude that gonad shielding is not applied to patients whilst not compromising the diagnostic quality of the image" (7).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations